Clinicopathological Factors of Hoarseness of Voice Presenting to Otorhinolaryngology OPD at A Tertiary Care Hospital - Bhandari, Chhanya; Paudel, Sanjaya; Upadhyay , Hari Prasad; Parajuli , Ramesh; Pokharel, Apar; Adhikari, Sabin; Rijal, Niranjan (Journal of College of Medical Sciences-Nepal, 2025)
Background Hoarseness is a common symptom with multiple causes presenting to ENT OPD. The purpose of the study was to determine the clinical and pathological causes of hoarseness so that early diagnosis and treatment could be made. The objective of this study is to evaluate the clinicopathological factors in patients with hoarseness presented to Otorhinolaryngology out patient department. Methods This analytical cross-sectional study was conducted in patients with hoarseness lasting for at least 3 weeks presenting to Otorhinolaryngology outpatient department during period of September 2024-July 2025 in College of Medical Sciences Teaching Hospital, Bharatpur, Nepal. The collection of data regarding patients’ demographics, nasopharyngolaryngoscopic findings, history of addiction to tobacco, alcohol or other drugs and histopathologic examination was done. Statistical analysis was done using frequencies, percentages and mean whenever applicable. Results We observed male dominance (68% male vs 32%, female), with mean age being 45.1 years. 44% patients with hoarseness had history of addiction. Nasopharyngolaryngoscopy findings included true vocal cord nodules in 36% and laryngopharyngeal reflux in 25% of cases. Among 45.45% of biopsies taken showed malignancy. Conclusions Hoarseness of voice is more common in middle age male and has frequent association with occupation and addiction to either tobacco, alcohol or both. Early identification and histopathological examination are crucial and malignancy should be suspected in patient with hoarseness with vocal cord masses.